The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s41936-022-00274-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different diets' nutrition on the fitness and hemocytic responses of the greater wax moth larvae, Galleria mellonella (Linnaeus) (Lepidoptera: Pyralidae)

Abstract: Background The greater wax moth, Galleria mellonella (L.) (Lepidoptera: Pyralidae), is the major devastating insect pest of beekeeping industry all over the world; however their larvae were valuable to be the most favorable alternative invertebrate model. For this purpose, new-hatched larvae were reared on five different nutritional diets based on: old wax-comb (natural food); wheat flour diet (Triticum aestivum L.); soybean diet (Glycine max); wheat germ diet; and date syrup diet (Phoenix dact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…It is clear that the food supplied in diets 2 and 3 efficiently produced a greater number of larvae with higher weights than natural beeswax. Previous studies were conducted to find the most suitable diets for rearing G. mellonella (Coskun et al 2006;Birah et al 2008;Huang et al 2010;Ellis et al 2013;Mohamed and Amro 2022). The suggested artificial diets in our study contained the same ingredients as the diets of Birah et al (2008) and Huang et al (2010) except for the absence of wheat bran and beeswax in our diets.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is clear that the food supplied in diets 2 and 3 efficiently produced a greater number of larvae with higher weights than natural beeswax. Previous studies were conducted to find the most suitable diets for rearing G. mellonella (Coskun et al 2006;Birah et al 2008;Huang et al 2010;Ellis et al 2013;Mohamed and Amro 2022). The suggested artificial diets in our study contained the same ingredients as the diets of Birah et al (2008) and Huang et al (2010) except for the absence of wheat bran and beeswax in our diets.…”
Section: Discussionmentioning
confidence: 88%
“…This concept was similar to the results observed previously by van Zyl and Malan (2015), Kotchofa and Baimey (2019) and Rahoo et al (2019) who found that the number of nematode production from G. mellon ella is proportional to the insect host body weight and size. Dadd (1963), Lee et al (2007), Shapiro-Ilan et al (2008 and Mohamed and Amro (2022) stated that the proportion and/or selection of ingredients in diets play a vital role in larval development, fitness and in turn the quality of nematodes. In this study, the multiplication of H. bacteriophora inside G. mellonella larvae was always greater than S. carpocapsae which agrees with that reported previously by Raj Kumar et al (2003).…”
Section: Discussionmentioning
confidence: 99%
“…Adults were mated and provided with 10% honey in a plastic container (13 × 17.5 × 7 cm). Egg masses were placed in a new container, each containing artificial diets for G. mellonella (Mohamed & Coppel, 1983) and S. litura (Gupta et al., 2005). All containers were kept at a temperature of 25 ± 2°C and 75 ± 5% relative humidity (RH) with a photoperiod of 12:12 (L:D).…”
Section: Methodsmentioning
confidence: 99%
“…The larvae were left for approximately 2 weeks until they were large enough to handle (40 mg). They were then individually placed in 24-well plates and provided with a nutritious artificial sterilized wheat-based diet ( 35 ) ( Supplementary Ta ble S1 ), where they were monitored until pupation. The pupae were then moved to medicine cups covered in cotton wool where the adults would eclose and remain until death.…”
Section: Methodsmentioning
confidence: 99%